2021
DOI: 10.1021/acsanm.1c01388
|View full text |Cite
|
Sign up to set email alerts
|

Crusty-Structured Cu@NiCo Nanoparticles as Anode Catalysts in Alkaline Fuel Cells

Abstract: The use of non-platinum group metal (non-PGM) catalysts and liquid fuels is a good way to reduce the burden of commercialization and supply in fuel cells. However, it is very difficult to reach the power performance of commercial hydrogen–air fuel cells, 1.0–1.2 W cm–2, with only non-PGM catalysts. In this study, we synthesize a crustlike Cu@NiCo/C nanocomposite as an anode catalyst for a direct liquid hydrazine fuel cell via facile polyol reduction by injecting a Ni–Co solution into a Cu solution. By systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Furthermore, the storage stability of the modified electrodes, which is critical for monitoring fuel concentration in alkaline media, was evaluated in a 1 M KOH solution containing 1 M hydrazine at a potential of −0.08 V for 500 s every day for seven days [see Figure 6b(i)] [46] . The sensor retained 85.18 % of its initial current response after seven days, indicating that it could be reused for up to six days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the storage stability of the modified electrodes, which is critical for monitoring fuel concentration in alkaline media, was evaluated in a 1 M KOH solution containing 1 M hydrazine at a potential of −0.08 V for 500 s every day for seven days [see Figure 6b(i)] [46] . The sensor retained 85.18 % of its initial current response after seven days, indicating that it could be reused for up to six days.…”
Section: Resultsmentioning
confidence: 99%
“…The well‐dispersed mixture was sprayed with an airbrush onto the MGL 190 (AvCarb) anode support and 29 BC (Sigracet) cathode support until the Pt loading reached 1 mg cm −2 . The anion exchange membrane used was the same as that used in our previous studies [46,49] . The size of a membrane electrode assembly (MEA) of 25 cm 2 (5 x 5 cm) was fabricated by hot‐pressing for 5 min at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering an alkaline medium for methanol oxidation, one of the challenging tasks is the choice of the catalyst. It has been reported that electrooxidation of methanol in alkaline media attains structure sensitivity [10], which has made a way for utilizing precious metals [12], other than platinum and platinum-modified catalysts, like Ni, Pd, Ag, Cu@NiCo, and some kinds of perovskite oxide catalysts [13][14][15][16][17]. Some recent report shows efficient iron based catalyst [18] and palladium based catalyst mixed with rhodium, which showed higher faradic current densities for methanol electrooxidation than Pt and Pt-based catalysts in alkaline fuel cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is vital to fabricate highly active, viable, and low-cost anode catalysts with a low overpotential for the demonstration of direct hydrazine fuel cells for different applications. In recent times, supported non-noble metal catalysts have been effectively prepared, and have progressively replaced the customary fuel cell catalysts that contain noble (precious) metals and their corresponding metal alloys in the electrooxidation reaction of hydrazine [29][30][31][32][33][34][35][36]. For instance, Duan and co-workers established a novel type of bendable electrode that was constructed using Cu nanocubes that were inserted into graphene paper via a simple electro-deposition process.…”
Section: Introductionmentioning
confidence: 99%